Análise da cobrança por serviços de limpeza pública: exemplos internacionais e o caso de Belo Horizonte - Bruno Ribas Alzamora (2019)
There has been an increase in the complexity and costs of providing urban waste management services. Thereby, with the backup of the laws 11.445/2007 and 12.305/2010, Brazilian municipalities have been attempting to charge for the services provision, in order to financially equalize the public budgets. However, they have been encountering difficulties in elaborating such charges, that are often being questioned by the citizens and the judiciary, many times being revoked for not satisfying the technical and legal criteria. Knowing that a fair and inclusive charging contributes to an environmentally efficient waste management, this study had the objective to study the many forms of charging and to propose elements that subside a new charging for the city of Belo Horizonte, Brazil, utilizing literature review, interviews, an analysis of governmental data. It was observed that the developed countries utilize the variable charging (PAYT), under its distinct forms, while the developing countries, including Brazil, are still trying to implement the charging, and are doing this through flat rates. The charging in Belo Horizonte, done by flat rate utilizing solely frequency of collection as a parameter, manages to reach a financial self-sufficiency o only 60%, and the ways it´s done does not contemplate the polluter pays and shared responsibility principles. As alterations proposals, it were suggested the tax division into a fix and variable rate, and the inclusion of the parameters water and electric energy consumption, constructed area and property use, besides the alteration of the charging vehicle, from the property tax bill to the water or energy bill. Thus, it is expected the new rate to be fairer, in a stronger harmony with the polluter pays principle, besides raising the income without the need to raise the tax prices. The PAYT schemes by weight, frequency and container were considered not feasible for Belo Horizonte, but in the future a charge made through the bag/sticker method is recommendable, for it´s the simplest and cheapest PAYT method, capable of bringing good results.